Role of melatonin in alleviating cold stress in Arabidopsis thaliana. Issue 3 (13th January 2014) - Bajwa, Vikramjit S.; Shukla, Mukund R.; Sherif, Sherif M.; Murch, Susan J.; Saxena, Praveen K.
Abstract Melatonin (N‐acetyl‐5‐methoxytryptamine) has been implicated in abiotic and biotic stress tolerance in plants. However, information on the effects of melatonin in cold‐stress tolerance in vivo is limited. In this study, the effect of melatonin was investigated in the model plant Arabidopsis thaliana challenged with a cold stress at 4⁰C for 72 and 120 hr. Melatonin‐treated plants (10 and 30 μm) had significantly higher fresh weight, primary root length, and shoot height compared with the nontreated plants. To aid in the understanding of the role of melatonin in alleviating cold stress, we investigated the effects of melatonin treatment on the expression of cold‐related genes. Melatonin up‐regulated the expression of C‐repeat‐binding factors (CBFs)/Drought Response Element Binding factors (DREBs), a cold‐responsive gene, COR15a, a transcription factor involved in freezing and drought‐stress tolerance CAMTA1 and transcription activators of reactive oxygen species (ROS)‐related antioxidant genes, ZAT10 and ZAT12, following cold stress. The up‐regulation of cold signaling genes by melatonin may stimulate the biosynthesis of cold‐protecting compounds and contribute to the increased growth of plants treated with exogenous melatonin under cold stress.